Blood-nerve barrier enhances chronic postsurgical pain via the HIF-1α/ aquaporin-1 signaling axis - Pei-zhi Wu; Ju Yao; Bei Meng; Yi-Bin Qin; Su Cao (BMC Anesthesiology, 2023)
Abstract Background Blood nerve barrier (BNB) participates in the development of neuropathic pain. AQP1 is involved in peripheral pain perception and is negatively correlated with HIF-1α phenotype, which regulates endothelial permeability. However, the role of HIF-1α-AQP1-mediated BNB dysfunction in Chronic Postsurgical Pain (CPSP) has not been reported. Methods Male Sprague-Dawley rats were randomized into 5 groups: (i) Naive group; (ii) Sham group; (iii) SMIR group: skin/muscle incision and retraction for one hour. Behavioral tests were performed for the three groups, BNB vascular permeability and western blotting were conducted to determine HIF-1α and AQP1 protein expression. (iv) The SMIR + HIF-1α inhibitor group; (v) SMIR + DMSO group. Rats in the two groups were administered with HIF-1α inhibitor (2ME2) or DMSO intraperitoneally on the third day post-SMIR surgery followed by performance of behavioral tests, BNB permeability assessment, and determination of HIF-1α, AQP1 and NF200 protein levels. Results The permeability of BNB was significantly increased and the expression of AQP1 was downregulated on the 3rd and 7th days post-operation. AQP1 is mainly located in neurons and NF200, CGRP-positive nerve fibers. HIF-1α was highly expressed on the third day post-operation. HIF-1α inhibitor reversed the decrease in AQP1 expression and increase in NF200 expression, barrier permeability and hyperalgesia induced by SMIR on the 3rd day post-surgery. Conclusions Early dysfunction of BNB mediated by HIF-1α/AQP1 activated by SMIR may be an important mechanism to promote acute postoperative painful transformation of CPSP. Preadaptive protection of endothelial cells around nerve substructures may be an important countermeasure to inhibit CPSP transformation. Early impairment of BNB function mediated by HIF-1α/AQP1 activated by SMIR may be an important mechanism for promoting acute postoperative pain transformation of CPSP.